Design and Implementation of a Wireless Sensor Network for Agricultural Applications - John, Jobish; S. Kasbekar, Gaurav; K. Sharma, Dinesh; Ramulu, V.; Shojaei Baghini, Maryam (EAI Endorsed Transactions on Internet of Things, 2018)
We present the design and implementation of a shortest path tree based, energy eﬃcient data collection wireless sensor network to sense various parameters in an agricultural farm using in-house developed low cost sensors. Nodes follow a synchronized, periodic sleep-wake up schedule to maximize the lifetime of the network. The implemented network consists of 24 sensor nodes in a 3 acre maize farm and its performance is captured by 7 snooper nodes for diﬀerent data collection intervals: 10 minutes,1 hour and 3 hours. The almost static nature of wireless links in the farm motivated us to use the same tree for a long data collection period (3 days). The imbalance in energy consumption across nodes is observed to be very small and the network architecture uses easy-to-implement protocols to perform diﬀerent network activities including handling of node failures. We present the results and analysis of extensive tests conducted on our implementation, which provide signiﬁcant insights.